2016
DOI: 10.22159/ijcpr.2017v9i1.16633
|View full text |Cite
|
Sign up to set email alerts
|

Study of Binding Interactions of Human Carbonic Anhydrase Xii

Abstract: Objective: The present study was carried out to study the binding interactions of different N'-(substituted phenyl sulfonyl)-pyridine-2-carbohydrazide derivatives and N'-(substituted phenyl sulfonyl)-thiophene-2-carbohydrazide derivatives which were synthesized by senior students from research laboratory, with objective to explore the suitability of selected ligands for their binding affinity for the selected target.Methods: Binding interactions of the selected ligands were studied using glide module of Schrod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…In this study, cellular tumor antigen p53, caspase 3, and mucosal addressin cell molecule 1 were successfully docked with apigenin using the BSP- Slim server. Based on the negative and lowest energy value (D G bind), the best docking orientation was chosen [30,31]. Docking analysis showed that there was a strong interaction between cellular tumor antigen p53 and apigenin.…”
Section: Protein-ligand Dockingmentioning
confidence: 99%
“…In this study, cellular tumor antigen p53, caspase 3, and mucosal addressin cell molecule 1 were successfully docked with apigenin using the BSP- Slim server. Based on the negative and lowest energy value (D G bind), the best docking orientation was chosen [30,31]. Docking analysis showed that there was a strong interaction between cellular tumor antigen p53 and apigenin.…”
Section: Protein-ligand Dockingmentioning
confidence: 99%